A forensically validated genetic toolkit for the species and lineage identification of the highly trafficked shingleback lizard (Tiliqua rugosa). (January 2023) - Brown, Amber O.; Ueland, Maiken; Stuart, Barbara H.; Frankham, Greta J.
Abstract: Shingleback lizards ( Tiliqua rugosa ) are among the most trafficked native fauna from Australia in the illegal pet trade. There are four morphologically recognised subspecies of shinglebacks, all with differing overseas market values. Shinglebacks from different geographic locales are often trafficked and housed together, which may complicate identifying the State jurisdiction where the poaching event occurred. Additionally, shinglebacks can be housed and trafficked with other species within the same genus, which may complicate DNA analysis, especially in scenarios where indirect evidence ( e.g. swabs, faeces) is taken for analysis. In this study, a forensic genetic toolkit was designed and validated to target shingleback DNA for species identification and geographic origin. To do this, field sampling across Australia was conducted to expand the phylogeographic sampling of shinglebacks across their species range and include populations suspected to be poaching hotspots. A commonly used universal reptile primer set (ND4/LEU) was then validated for use in forensic casework related to the genus Tiliqua . Two additional ND4 primer sets were designed and validated. The first primer set was designed and demonstrated to preferentially amplify an ∼510 bp region of the genus Tiliqua over other reptiles and builds on existing data to expand the available phylogeographic database. The second primer set was designed and demonstrated to solely amplify an ∼220 bp region of T. rugosa ND4 over any other reptile species. Through the validation process, all primers were demonstrated to amplify T. rugosa DNA from a variety of sample types ( e.g. degraded, low quality and mixed). Two of the primer sets were able to distinguish the genetic lineage of T. rugosa from the phylogeographic database. This work provides the first forensically validated toolkit and phylogeographic genetic database for Squatmate lizards. Highlights: Validated mitochondrial DNA toolkit for Shingleback lizard trafficking casework. Established Shingleback phylogeographic genetic database. Identified five Shingleback phylogeographic lineages. Identified lineages of Shinglebacks confiscated from the illegal wildlife trade.